Interfaces, Circuits and Humidifiers - Ferreira, Rosario (Frontiers in Pediatrics, 2020)
Long term non-invasive ventilation (LTNIV) has been increasingly used in children to manage chronic respiratory failure and airway obstruction. Interfaces are of paramount importance for non-invasive ventilation (NIV) effectiveness and patient compliance. However, historically the choice of pediatric mask has been limited by the scarce availability of commercial interfaces. In recent years, an increasing number of different masks have been commercialized for children, allowing to increase the number of patients that could benefit from LTNIV. Factors as the age of the child, disease, craniofacial conformation, type of ventilator and mode of ventilation and children’s and family preferences should be taken into account when selecting the appropriate mask. Adverse events such as skin lesions, facial growth impairment and leaks must be prevented and promptly corrected. Humidification is a controversial issue on NIV but it may be useful in certain circumstances. Regular cleaning and disinfection of interfaces and equipment must be addressed. During follow-up, educational programs, close supervision and continuous support to children and families are crucial to the success of LTNIV therapy.